Effect of a communication intervention on alcohol use during pregnancy in post conflict Northern Uganda: a quasi experimental study - Apophia Agiresaasi; Goretti Nassanga; Gakenia Wamuyu Maina; Juliet Kiguli; Elizabeth Nabiwemba; Noah Kiwanuka; Aggrey Mukose; Nazarius Mbona Tumwesigye (BMC, 2022)
Abstract Background Alcohol use during pregnancy is a preventable risk factor for Fetal Alcohol Spectrum disorders. Psycho-social and educational interventions have been reported to enable women reduce alcohol intake levels during pregnancy and help improve some health outcomes of unhealthy alcohol use. We set out to assess the effect of a communication intervention on alcohol use during pregnancy in post conflict northern Uganda. Methods The study employed a quasi - experimental design to assess the effect of a community health worker led communication strategy on pregnant women's knowledge, attitudes and various patterns of alcohol use using Difference in Difference(DiD). 420 respondents were recruited at baseline as at endline. Results The communication messages were significantly associated with reduced odds of binge drinking (P = 0.018; OR = 0.09; CI = 0.012-0.66). Also those who received the intervention were less likely to drink frequently (P = 0.80; OR = 0.75; 95%CI = 0.074-7.5) or be harmful alcohol users(P = 0.948). The intervention also positively influenced having fair (β =0.49;P = 0.217;RRR =1.63)or adequate knowledge(β = 0.89;P = 0.25;RRR = 2.44) and having positive(β = 0.37;RRR =1.44;P = 0.46) or fair attitude(β = 0.19;RRR = 1.21; P = 0.693) although not to a significant level. Conclusions The communication intervention affected some patterns of alcohol use among pregnant women and not others. Our results contribute to existing evidence that communication interventions are a promising approach in reduction of alcohol exposed pregnancies. Interventions aimed at promoting alcohol abstinence during pregnancy should be implemented alongside other strategies that address factors that influence pregnant women to drink to achieve maximum results.